2019
DOI: 10.3390/pharmaceutics11030120
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Core-Shell System-Based Iron Oxide Nanoparticle Coated with Biocompatible Copolymer for Anticancer Drug Delivery

Abstract: Polymer coating has drawn increasing attention as a leading strategy to overcome the drawbacks of superparamagnetic iron oxide nanoparticles (SPIONs) in targeted delivery of anticancer drugs. In this study, SPIONs were modified with heparin-Poloxamer (HP) shell to form a SPION@HP core-shell system for anticancer drug delivery. The obtained formulation was characterized by techniques including transmission electron microscopy (TEM), Fourier transform infrared spectra (FT-IR), vibration sample magnetometer (VSM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 36 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…The fact, that DOX coupled to MNPs is basically able to interact with DNA is corroborated by: (1) the knowledge that upon degradation in lysosomes DOX is released from the MNPs, and as a free molecule DOX is able to migrate to the cell nucleus [ 36 ]; (2) previous investigations showing that DOX-loaded MNPs (e.g., electrostatic coupling; in absence of hyperthermia) exert a low intrinsic cytotoxicity [ 27 , 36 , 37 ]; and (3) the tumor reducing effect of our covalently coupled DOX-MNPs (4 µmol DOX/g Fe) is lower compared to that of the electrostatically coupled ones (40 µmol DOX/g Fe, [ 27 ]). All mentioned relationships indicate that the tumor reducing effect of our DOX-functionalized MNPs was due to a synergistic mechanism between DOX and hyperthermia, even though the comparably lower antitumor effect compared to the electrostatic MNP functionalization in former studies might well be due to a reduced number of DOX molecules per mg Fe and also due to the fact that covalent conjugation attenuates the release of DOX from the MNPs to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The fact, that DOX coupled to MNPs is basically able to interact with DNA is corroborated by: (1) the knowledge that upon degradation in lysosomes DOX is released from the MNPs, and as a free molecule DOX is able to migrate to the cell nucleus [ 36 ]; (2) previous investigations showing that DOX-loaded MNPs (e.g., electrostatic coupling; in absence of hyperthermia) exert a low intrinsic cytotoxicity [ 27 , 36 , 37 ]; and (3) the tumor reducing effect of our covalently coupled DOX-MNPs (4 µmol DOX/g Fe) is lower compared to that of the electrostatically coupled ones (40 µmol DOX/g Fe, [ 27 ]). All mentioned relationships indicate that the tumor reducing effect of our DOX-functionalized MNPs was due to a synergistic mechanism between DOX and hyperthermia, even though the comparably lower antitumor effect compared to the electrostatic MNP functionalization in former studies might well be due to a reduced number of DOX molecules per mg Fe and also due to the fact that covalent conjugation attenuates the release of DOX from the MNPs to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that covalent binding of drugs can enable slow drug release at the targeted site. A functionalization that permits only adsorption can lead to premature drug release [ 33 , 46 , 80 ].…”
Section: Reviewmentioning
confidence: 99%
“…Depending on the type of emulsifier used, the coating can be hydrophilic or hydrophobic, but it is common to use hydrophilic polymers, such as PVA or PEG, for drug release studies [ 33 , 76 ] because the hydrophobic polymers are rapidly uptaken by macrophages [ 85 ]. SPIONs coated with a mixture of PVA and polyvinyl amine were shown to induce very active mitochondrial and endocytic processes in cells and to be highly toxic to cells due to the positive charge of the amine groups.…”
Section: Reviewmentioning
confidence: 99%
“…5. From Figure 5, one can see that Fe 3 O 4 NPs, TSC@Fe 3 O 4 and SiO 2 coated Fe 3 O 4 NPs are all superparamagnetic because no hysteresis loop can be observed [13][14][15][16]. The saturation magnetization of Fe 3 O 4 NPs is 45.8 emu/g, which is higher than that of TSC@Fe 3 O 4 (~14.6 emu/g), SiO 2 coated Fe 3 O 4 NPs (~13.4 emu/g) due to the functionalization and the thick silica shell layer (~ 15 nm), respectively.…”
Section: Magnetic Propertiesmentioning
confidence: 99%